The Influence of Political Gimmicks as a Campaign Strategy in the Society 5.0 Era on New Voters in Semarang City - Alvi Lutviah Amini; Chandra Sivano; Elang Samudra; Charist Marvell Geraldo; Ray Fazle Rahman; Eni Rahmawati (Forum Ilmu Sosial)
The digital era has significantly transformed political interactions, particularly through social media as a communication platform. Political gimmicks have become a new trend in campaign communication, especially to attract first-time voters in the Society 5.0 era. This research aims to identify its impact on the trust of first-time voters. A quantitative method was used for data collection, conducted by surveying 400 first-time voters in Semarang City. A simple linear regression test results show that political gimmicks significantly affect first-time voters' trust, with a significance value of 0.002 < 0.05. This study emphasizes voter political literacy's importance in ensuring rational and informed political decisions. The research plays a crucial role in understanding the dynamics of political communication in the digital era and the critical role of first-time voters in maintaining the quality of democracy.